The Financial Crisis and Diverging House Prices: Evidence from the Copenhagen Metropolitan Area - Ismir Mulalic; Holger Rasmussen; Jan Rouwendal; Hans Henrik Woltmann (Tinbergen Institute, 2017)
This paper investigates the development of house prices in Copenhagen in the period 1994-2013, while paying special attention to the heterogeneous impact of the boom and bust periods along the dimensions of housing type (single vs multifamily housing), geography and quality. To allow for price developments that can differ by quality, we use a recently developed generalization of the conventional Muth model that assumes a constant unit price across the quality spectrum. It allows us to separately consider the development of house prices and quality in Copenhagen neighbourhoods. Moreover, we investigate the validity of the common assumption of a constant unit price and reject it decisively. We use detailed housing transaction data for the greater Copenhagen area. We show that the housing boom of the 2000's and the bust that followed hit the lowest quality segments significantly harder than the high quality segments of the housing market.
Keywords: D40; L85; R21; R31; 330; housing price; housing quality; housing price index